SIMULATION OF DIRECT GEOREFERENCING FOR GEOMETRIC SYSTEMATIC CORRECTION ON LSA PUSHBROOM IMAGER - Muchammad Soleh; Wismu Sunarmodo; Ahmad Maryanto (International Journal of Remote Sensing and Earth Sciences (IJReSES), 2017)
LAPAN has developed remote sensing data collection by using a pushbroom linescan imager camera sensor mounted on LSA (Lapan Surveillance Aircraft). The position accuracy and orientation system for LSA applications are required for Direct Georeferencing and depend on the accuracy of off-the-shelf integrated GPS/inertial system, which used on the camera sensor. This research aims to give the accuracy requirement of Inertial Measurement Unit (IMU) sensor and GPS to improve the accuracy of the measurement results using direct georeferencing technique. Simulations were performed to produce geodetic coordinates of longitude, latitude and altitude for each image pixel in the imager pushbroom one array detector, which has been geometrically corrected. The simulation results achieved measurement accuracies for mapping applications with Ground Sample Distance (GSD) or spatial resolution of 0,6 m of the IMU parameter (pitch, roll and yaw) errors about 0.1; 0.1; and 0.1 degree respectively, and the error of GPS parameters (longitude and latitude) about 0.00002 and 0.2 degree. The results are expected to be a reference for a systematic geometric correction to image data pushbroom linescan imager that would be obtained by using LSA spacecraft.